GRIEF OF THE LAND AND NATION - Zebo Kabilova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article talks about the articles in the first issue of Yurt magazine by Ashurali Zahiri, who was among the intellectuals of Turkestan and took an active part in the revolutionary movements.